Speciation process on Brazilian continental islands, with the description of a new insular lancehead of the genus Bothrops (Serpentes, Viperidae). Issue 1 (31st December 2022) - Barbo, Fausto E.; Booker, William W.; Duarte, Marcelo R.; Chaluppe, Betina; Portes-Junior, José A.; Franco, Francisco L.; Grazziotin, Felipe G.
Abstract : Brazilian continental islands represent a natural laboratory to study speciation driven by recent phenotypic and genotypic divergence. The Bothrops jararaca species group is distributed in the Brazilian Atlantic Forest and on most of the Brazilian continental islands. The group is currently composed of the mainland common lancehead ( B. jararaca ) and four insular species ( B. alcatraz, B. insularis, B. otavioi, and B. sazimai ). Here, we evaluate mitochondrial DNA and morphological diversity of the B. jararaca species group and aim to provide additional evidence to understand insularization processes on the Brazilian coast. Our results, interpreted together with a comprehensive review of geomorphological data, provide a new conceptual framework for understanding the colonization process of the Brazilian continental islands. This framework suggests a history of multiple rounds of periodic isolation and reconnection between insular populations and their mainland relatives throughout the last 420, 000 years. Furthermore, although some insular populations may have speciated prior to the last glacial maximum, other species likely diverged within the last 11, 000 years. Additionally, the repeated evolution of size and dietary shift in the B. jararaca species group suggests a remarkable case of convergent adaptation. Our study provides evidence that the Bothrops from Ilha da Moela (Brazilian state of São Paulo) represents an undescribed species, presenting a distinct phenotype, and an exclusive history of isolation and adaptation. We describe this unique lancehead as a new species and we suggest it should be listed as critically endangered based on its endemicity to a small island that is severely impacted by constant and longstanding human presence. http://zoobank.org/urn:lsid:zoobank.org:pub:B1F65287-CEC4-4F9C-90D7-42314A497590